The evils of polygyny : evidence of its harm to women, men, and society - McDermott, Rose, 1962- (Cornell University Press, 2018)
"One powerful structural factor which enforces and replicates patterns of male dominance is the practice of polygyny, which is shown by data to be harmful to women, children, men, and society"-- Provided by publisher.
Keywords: Polygyny.; Male domination (Social structure); Women -- Violence against.; Polygynie.; Domination masculine (Structure sociale); Femmes -- Violence envers.; SOCIAL SCIENCE -- Gender Studies.; POLITICAL SCIENCE -- Public Policy -- Cultural Policy.; SOCIAL SCIENCE -- Anthropology -- Cultural.; SOCIAL SCIENCE -- Popular Culture.; Polygyny; Women -- Violence against; polygamy, women's rights, moral and cultural relativism, psychology.; Electronic book.